Knowledge of Malaria Management in Pediatrics among Undergraduate Pharmacy Students in University of Ibadan, Nigeria (2022)
Background Falls are a major cause of morbidity and hospitalization in older people. Many drugs have been shown to increase the risk of falls in this population. Few empirical data exist on the use of fall-risk-increasing drugs among older people of sub-Saharan Africa countries. Objective This study aimed to assess the prevalence and predictors of falls, and the association between FRIDs, drugs causing orthostatic hypotension and falls. Setting Geriatric center, University College Hospital, Ibadan, Nigeria. Methods A cross-sectional study of 400 older patients aged ≥ 60 years selected consecutively at the geriatric centre, between September and November 2019, were interviewed using a semi-structured questionnaire. Socio-demographic information, medication utilization, and history of falls were obtained. Bivariate and multivariate analyses were carried out using SPSS 23. Alpha was set at 0.05. Main outcome measure Prevalence and predictors of falls among ambulatory older patients. Results The mean age of the older patients was 72.4 ± 7.3 years and 255 (63.7%) were females. The total number of FRIDs and ODs used by older patients was 578 (35.2%). The prevalence of fall was 181 (45.3%) which was signifcantly higher among the females compared with the males (51.8% vs 33.8%) p = 0.01. Classes of medications such as anti-Parkinson’s (p = 0.027), sedatives (p = 0.033), antipsychotics (p = 0.011) and anticholinergic (p = 0.027) were signifcantly associated with fall. Predictive factors for falls on logistic regression were female [OR = 2.375; 95% CI 0.274–3.704, p = 0.001] and use of antipsychotics [OR = 5.132; 95% CI 1.352–19.480, p = 0.016]. Conclusion The prevalence of falls was high and being a woman ≥ 60 years is a major risk factor for falling. Interventions to decrease falls in older patients by drug modifcation and deprescribing of FRIDs and ODs might reduce fall-related injuries. Thus, a multidisciplinary approach is essential for intervention to reduce the risk of falls and improve therapeutic outcomes among older patients.